2018
DOI: 10.1016/j.newast.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized strange quark matter in f ( R, T ) gravity with bilinear and special form of time varying deceleration parameter

Abstract: In this paper, we have studied homogeneous and anisotropic locally rotationally symmetric (LRS) Bianchi type-I model with magnetized strange quark matter (MSQM) distribution and cosmological constant Λ in f (R, T ) gravity where R is the Ricci scalar and T the trace of matter source. The exact solutions of the field equations are obtained under bilinear and special form of time varying deceleration parameter (DP). Firstly, we have considered two specific forms of bilinear DP with a single parameter of the form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 67 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…. Hence our results resembles with the work investigated by those of Sahoo at al. (2018), Chirde and Shekh (2018).…”
Section: Physical Parameters Of Isotropic Frw Line Elementsupporting
confidence: 93%
See 1 more Smart Citation
“…. Hence our results resembles with the work investigated by those of Sahoo at al. (2018), Chirde and Shekh (2018).…”
Section: Physical Parameters Of Isotropic Frw Line Elementsupporting
confidence: 93%
“…where B c is the bag constant. Recently,Sahoo et al (2018) studied homogeneous and anisotropic locally rotationally symmetric Bianchi type-I model with magnetized strange quark matter together with cosmological constant (Λ) in f (R, T ) gravity by considering two specific forms of bilinear deceleration parameter and obtained in the early universe magnetic flux has more effects and it reduces gradually in the later stage while behavior of strange quark matter along with magnetic epoch gives an idea of accelerated expansion of the universe as per the observations of the type-Ia Supernovae. Chirde and Shekh (2018) investigated plane symmetric cosmological model with quark and strange quark matter in the deformations of the Einsteins theory of general relativity where a proper deformation of general relativity in the ultraviolet regime could play the role of describing the transition between general relativity and quantum gravity and revealed that the strange quark matter gives an idea of existence of dark energy in the universe and supports the observations of the type-Ia Supernovae.…”
mentioning
confidence: 99%
“…It gives us the rate of expansion of the universe that q > 0 deceleration, q < 0 acceleration and q = 0 constant rate of expansion. It is noted that there are many studies related to the time varying deceleration parameter for Bianchi type space-time in different gravitational theories [37][38][39]. In our case the deceleration parameter obtained as…”
Section: Noether Symmetry and Exact Solutionmentioning
confidence: 64%
“…Moreover, Sahoo et al have investigated MSQM in f (R, T ) theory [18]. Besides, some scientists have investigated MSQM and SQM [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%